Paradoxical phenomenon of leadership - Romanovskiy, A. G.; Ponomaryov, O. S. (Problems of Engineer-Pedagogical Education, 2018)
Leadership phenomenon is interesting because most people are quite voluntarily accept some power over the leader himself and his actions are based on the influence of its psychological impact. But the analysis of the phenomenon of leadership is also evidence of the presence, and other characteristics of leadership. One of them is the fact that its function as a social phenomenon is often accompanied by various manifestations of paradoxes. They are made in unusual, unexpected actions and decisions of the leader who is often sharply at odds with the generally accepted ideas, and even common sense. This manifestation of the paradoxical nature of leadership are not yet sufficiently studied. Paradoxes are found in the decisions and actions of the leaders, in their statements and actions, behavior and lifestyle. Most often it is the paradoxes provide leaders to effectively address the complex problem situations. The reason is the difference between the paradoxes of mental and intellectual qualities of the leaders of the common people. One of these differences is in a special vision and the leaders of the assessment not only of problematic situations, but also everyday things and phenomena. This vision is determined by the compound of the leaders in-depth knowledge, experience and developed intuition. However, many features of the manifestation of the life and activity leaders consider the norm, while the majority of other people, they seem to be paradoxical. A striking example of this paradox is that many leaders can successfully lead the various groups and people to ensure the achievement of the purposes of their joint activity, not only having a formal governmental authority, but not carrying the usual administrative functions. Special efficiency paradox demonstrates leadership in innovative stage in the development of human civilization.